Intermittent right upper extremity ischemia in a patient with simultaneous aberrant right subclavian artery and patent foramen ovale: A case report - Pouya Tayebi; Mahdi Davoodi; Fatemeh Mahmoudlou (Babol University of Medical Sciences, 2021)
Background: Upper extremity intermittent ischemia due to non-aneurysmal, not occluded aberrant right subclavian artery (ARSA) is rare. Case presentation: We describe a 30-year-old male who suffered from PFO and non-aneurysmal, not occluded ARSA, and presented by intermittent right upper extremity ischemia. He was treated by right carotid subclavian transposition for ARSA and antiplatelet medication for PFO. Conclusion: Authors assume that intermittent limb ischemia can occur secondary to anatomical changes in a patient without aneurysmal degeneration or occluded ARSA and the existence of pure PFO without any evidence of venous thrombosis is not enough to prove the paradoxical emboli scenario.